Pengembangan Ensiklopedia Peralatan Laboratorium Biologi SMA/MA sebagai Sumber Belajar Biologi Siswa Kelas X di SMA Negeri 16 Semarang - Muhammad Miftahul Huda; Ruswan Ruswan; Saifullah Hidayat (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2018)
This study aims to produce an encyclopedia of biological laboratory equipment and to find out the feasibility of the encyclopedia of biological laboratory equipment developed as a biology learning resource for high school students. This study included research and development (R D) using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) developed by Reiser and Mollenda in the 1990s. This research is limited only to the implementation stage (limited or small scale implementation), then limited testing is conducted to 1 material expert, 1 media expert, 2 biology teachers and 4 peer reviewers and 20 students' responses to the product developed to determine the quality/feasibility of the product. The research instrument was in the form of a check list questionnaire using a Likert scale. The design of this study uses a descriptive qualitative research design with the type of data in the form of qualitative and quantitative data to determine the quality/feasibility of the product being developed. the results showed that: encyclopedia products of biology laboratory equipment were developed with the ADDIE model. The quality/feasibility of the encyclopedia is developed based on the assessment of material experts with a percentage of 80% including the good category (B); media experts at 85.6% including the excellent category (SB); biology teachers at 91% including the excellent category (SB); peer reviewers at 86.8% including the excellent category (SB); and student responses of 87.6% included very feasible categories. Thus it can be concluded that the encyclopedia of biological laboratory equipment developed having very decent quality is used as a reference for teachers in biology laboratory as well as can be used by high school students as one of the learning resources of biology.